EVALUASI KETERSEDIAAN PETA PADA SITUS WEB RESMI KEMENTERIAN DAN LEMBAGA PEMERINTAH INDONESIA - , ZULFAN NAZAL ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The advancement of internet technology makes the accessibility and utilization of information become quicker and cheaper. Using internet as dissemination media of public information is implementation of law 11/2008 and law 14/2008 which the goal is to make information dissemination quicker, cheaper and can accessed from anywhere. This research aimed to survey map availability in official websites of 34 Indonesian Government Ministries and 28 Indonesian Government Agencies. Further, it aimed to evaluate their quality from cartographic aspect and maps readability. Passive method is used in this research, in which researcher evaluate the map without any correspondence. The map evaluation is based on visual evaluation of map type and readability level and checklist information to compare the information of maps with standard of visual information of maps like title, north arrow, scale, projection system, grid, legend, data source and map maker. The result shows that the government was not concerns with map availability and its quality. There were only several official website of Indonesian Government Ministries and Agencies that have map and even fewer who have informative maps. Of the 34 institution of Indonesian Government Ministries and Agencies who have maps, there are 100.205 maps with more than 99% are readable but only 8 institution have map and fulfilled good category.